2009
DOI: 10.1677/joe-09-0262
|View full text |Cite
|
Sign up to set email alerts
|

TSH receptor activation and body composition

Abstract: The impacts of hyper and hypothyroidism on body composition, i.e. the relative quantity and quality of bone, adipose tissue and muscle, have traditionally been attributed uniquely to abnormal levels of free thyroid hormones. The presence of biologically active TSH receptors in bone, fat and muscle, raises the possibility that both thyroid hormones and TSH contribute to the changes in body composition associated with thyroid disease. This review evaluates the evidence for this in terms of the in vitro experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 86 publications
0
32
0
1
Order By: Relevance
“…We studied D2, D3, and TSHR expression in muscle tissue and observed no prominent differences between GPB5 Ϫ/Ϫ and WT mice. Previous studies had suggested that muscle TSHR mRNA expression resulted from expression in fibroblasts rather than myocytes (10). We stimulated a skeletal muscle cell line with TSH, thyrostimulin, or GPB5.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We studied D2, D3, and TSHR expression in muscle tissue and observed no prominent differences between GPB5 Ϫ/Ϫ and WT mice. Previous studies had suggested that muscle TSHR mRNA expression resulted from expression in fibroblasts rather than myocytes (10). We stimulated a skeletal muscle cell line with TSH, thyrostimulin, or GPB5.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the thyroid gland, TSHR expression has been reported in a number of peripheral tissues including WAT, BAT, muscle, kidney, skin, and bone (10). Activation of the TSHR is known to regulate deiodinase expression and activity in several tissues (6, 11-13, 23, 28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, T4 is a pro-hormone of the biologically active T3 (19,20). A recent study on human osteoblast cell line showed increased expression of deiodinase 2 (which converts T4 to T3) by administration of TSH, suggesting that TSH may indirectly promote bone turnover by increasing local T3 availability (21). Furthermore, the HPT axis set-point in an individual is at least in part genetically determined and may influence fracture risk (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…These two conditions have been associated with opposing effects on human BMD. Specifically, while hyperthyroidism is traditionally associated with low BMD, TSHR gain-of-function has been associated with high BMD (de Lloyd et al, 2010); it was unknown whether opallus exhibited an axial skeletal phenotype. In a first cohort where we performed an initial screen of n = 2 fish ( Figure 9A), we observed a clear increase in TMD in opallus that was not present in standard length matched AB controls, or in another mutant derived in a forward genetic screen that exhibits pigmentation defects, pissarro (Quigley et al, 2004) (SL of AB: 23.7 ± 1.1 mm, SL of opallus: 24.3 ± 1.4 mm, SL of pissarro: 23.7 ± 0.1 mm, mean ± SD).…”
Section: Identification Of Opallus As a Novel Axial Skeletal Mutantmentioning
confidence: 99%